Development progeria the role of institutions and the exchange rate - Daway, Sarah Lynne S.; Fabella, Raul V. ([Quezon City] School of Economics, University of the Philippines, 2015)
Convergence is more the exception than the rule in the development landscape. As a possible explanation, we posit development progeria: the phenomenon where a low-income country exhibits the industrial share dynamics of high-income mature economies where the Non-traded Goods Sector outgrows the Traded Goods Sector and the share of the non-traded goods sector outstrips the share of the traded goods sector. We argue that this seems to be the case of the Philippines in the last 25 years.
Title was 'Philippine Review of Business and Economics' until 1979. Title changed to 'Philippine Review of Economics and Business' from 1980-2000, and again changed to 'Philippine Review of Economics' since 2001.
Includes bibliographical references (pages 114-116)
Keywords: Economic development -- Philippines; Philippines -- Economic history